THE PHENOMENOLOGICAL APPROACH IS THE KEY TO UNDERSTANDING THE SPREAD AND TRANSFORMATION OF SUFISM IN THE WEST - Muminov, Nozim (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the author examines the phenomenology of Sufism as one of the markers of religious identity. The author of the article believes that the phenomenological approach, along with other scientific approaches, is becoming relevant in describing Sufism in the conditions of Western secular civil society. The example of Western Sufism and its tolerance reveals a new paradigm of the phenomenology of Sufism, which spread in Western countries at the end of the 19th and throughout the 20th centuries. The theses of the article reflect aspects of Western Sufism as a new spiritual resource of Western society. The results of a study conducted in 2002 in the USA are taken as a basis.